Combining Energy Transfer and Optimized Morphology for Highly Efficient Ternary Polymer Solar Cells. Issue 13 (17th February 2017) - Zhao, Fuwen; Li, Yang; Wang, Zaiyu; Yang, Yang; Wang, Zhen; He, Guiying; Zhang, Jianqi; Jiang, Li; Wang, Taishan; Wei, Zhixiang; Ma, Wei; Li, Bao; et al.
Abstract : Aimed at achieving ideal morphology, illuminating morphology–performance relationship, and further improving the power conversion efficiency (PCE) of ternary polymer solar cells (TSCs), a ternary system is designed based on PTB7‐Th:PffBT4T‐2OD:PC71 BM in this work. The PffBT4T‐2OD owns large absorption cross section, proper energy levels, and good crystallinity, which enhances exciton generation, charge dissociation and transport and suppresses charge recombination, thus remarkably increasing the short‐circuit current density ( J sc ) and fill factor (FF). Finally, a notable PCE of 10.72% is obtained for the TSCs with 15% weight ratio of PffBT4T‐2OD. As for the working mechanism, it confirmed the energy transfer from PffBT4T‐2OD to PTB7‐Th, which contributes to the improved exciton generation. And morphology characterization indicates that the devices with 15% PffBT4T‐2OD possess both appropriate domain size (25 nm) and enhanced domain purity. Under this condition, it affords numerous D/A interface for exciton dissociation and good bicontinuous nanostructure for charge transport simultaneously. As a result, the device with 15% PffBT4T‐2OD exhibits improved exciton generation, enhanced charge dissociation possibility, elevated hole mobility and inhibited charge recombination, leading to elevated J sc (19.02 mA cm −2 ) and FF (72.62%) simultaneously. This work indicates that morphology optimization as well as energy transfer plays a significant role in improving TSC performance. Abstract : Ternary polymer solar cells based on PTB7‐Th:PffBT4T‐2OD:PC71 BM are designed according to the complementary properties of PTB7‐Th and PffBT4T‐2OD. The highest efficiency of 10.72% for this ternary system is achieved with 15% PffBT4T‐2OD. As for the working mechanism, this ternary system paves the way to investigate the morphology–performance relationship. Moreover, the energy transfer is involved in ternary blend.